DEVELOPMENT OF PROFESSIONAL COMPETENCE OF FUTURE TEACHERS BY MEANS OF SPIRITUAL IDEALS THEORETICAL AND METHODOLOGICAL FOUNDATIONS (Scientific journal of the Fergana State University, 2025)
This article focuses on the model of ideal human thinking, the symbol of perfection, the norm, the analysis of internal characteristics of moral, religious, socio-political and aesthetic ideals, the formation of definitions of the meaning and content of the concept of ideal.